Quantitative Competitive Reverse Transcription-PCR for Quantification of Dengue Virus RNA - Wang, Wei-Kung (American Society for Microbiology, 2000)
A quantitative competitive reverse transcription-PCR assay was developed to quantify dengue virus RNA in this study. The main features include a primer pair targeting a highly conserved region in the capsid and the addition of competing RNA that contains an internal deletion to provide a stringent internal control for quantification. It can be utilized to quantify RNA isolated from the four dengue virus serotypes but not RNA isolated from other flaviviruses, including Japanese encephalitis virus and hepatitis C virus, both prevalent in Asia. It can also be used to quantify dengue virus RNA isolated from the plasma of infected individuals. The sensitivity of the assay was estimated to be 10 to 50 copies of RNA per reaction, and twofold differences in virus titer are distinguishable. This assay is a convenient, sensitive, and accurate method for quantification and can be used to further understanding of the pathogenesis of dengue virus infection.